Use of a commercial feed supplement based on yeast products and microalgae with or without nucleotide addition in calves - Aristide Maggiolino; Gerardo Centoducati; Elisabetta Casalino; Gabriella Elia; Tiziana Latronico; Maria Grazia Liuzzi; Luigi Macchia; Geoffrey E. Dahl; Gianluca Ventriglia; Nicola Zizzo; Pasquale De Palo (Journal of Dairy Science, 2023)
ABSTRACT: The use of feed additives with antioxidant and immune response modulatory activity could be a useful strategy in suckling calves to reduce morbidity and mortality. This strategy is based on several feed additives tested for these purposes. The aim of the paper is the examination of a commercial feed additive for adult cows for use in calves, with and without nucleotide supplementation. Seventy-five Holstein Friesian male calves were divided in 3 groups, with each calf randomly assigned to a group according to birth order. All calves received 2 L of pooled colostrum within 2 h of birth. The commercial feed supplement group was orally administered with 5 g/head of Decosel (dried brewer's yeast lysate (Saccharomyces cerevisiae), brewer's yeast walls (Saccharomyces cerevisiae), diatoms, spirulina, barley flour, calcium carbonate; Agroteam srl, Torrimpietra, Italy) and the nucleotides + commercial feed supplement group was orally administered with 5 g/head of an additive containing 2.5 g of Decosel and 2.5 g of nucleotides once daily from birth to 25 d. The control group was orally administered 20 mL of fresh water/head once daily. Calves that received the supplement and the nucleotides showed lower rates of protein and metabolizable energy conversion, with longer villi and greater crypt depth in duodenum. Moreover, the commercial feed supplement alone increased antioxidant capacity [2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and ferric-reducing antioxidant power] in plasma some activity of antioxidant liver enzymes, and peripheral blood mononuclear cell viability after in vitro concanavalin A and H2O2 stimuli. Dietary supplementation with a commercial feed supplement containing yeast products (yeast cell walls and hydrolyzed yeast) and microalgae enhanced the redox balance and gut morphology in calves, allowing calves to improve their immune response, increasing resistance to stress. Moreover, these beneficial effects were strongly potentiated when dietary nucleotides were added to the supplement.